Representation of the ecological crisis impact in Sumur, a short story written by Eka Kurniawan - Setiyoningsih, Titi; Suwandi, Sarwiji; Wardani, Nugraheni E.; Ulya, Chafit; Setyawan, Eko; Zulianto, Sugit (citeus, 2024)
The ecological crisis is getting worse over time, resulting in various problems. The ecological crisis is widely represented in literary works but not much has been studied regarding its impact so it needs to be explained in depth. This study aimed to describe the impact of the ecological crisis represented in “Sumur”, a short story by Eka Kurniawan. The data of this research were words, phrases, clauses, sentences, paragraphs, and discourse in the short story. The data collection technique was a document analysis using the theory of ecocriticsm. The data validity technique used theoretical triangulation through data validity activities based on various theoretical perspectives. The novelty of the research was that no one had previously analyzed the ecocriticism in the short story before. The data analysis technique used interactive analysis. The findings indicated that the impact of the ecological crisis represented in